الأمن الثقافي في ظل تحديات العولمة:دراسة حالة منطقة المغرب العربي - تبينة, راوية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يشكل الأمن الثقافي أحد المقومات الأمن القومي لأي دولة انطلاقا أنه يمثل معالم الهوية الوطنية، و بالتالي فهو مصدر استمرار بقاء الدول ،خاصة في ظل التهديدات الجديدة وعلى رأسها العولمة التي تحاول بكل الطرق دحض الثقافة، ومن هذا المنطلق سوف تختص دراستنا هذه بمعالجة إشكالية محورية تتمثل في إلقاء الضوء على جملة التحديات التي تفرضها العولمة الثقافية على دول منطقة المغرب العربي ،ولمعالجة هذا الموضوع اقتضت الدراسة الاستعانة بالمنهج الوصفي التحليلي من خلال رصد وتحليل جل القيود التي تفرضها العولمة الثقافية على منطقة العربي وهذا للوصول إلى الحلول والسبل الناجعة التي تحمي هذه الأخيرة من خطر طمس معالم الهوية. Cultural security is one of the components of national security for any country based on the fact that it represents the features of national identity, and therefore it is the source of the continued survival of countries, especially in light of the new threats, especially globalization, which is trying in every way to refute the authentic culture, and from this point of view, our study will be concerned with addressing a pivotal problem of throwing To address this issue, the study required the use of the descriptive analytical approach by monitoring and analyzing most of the restrictions imposed by cultural globalization on the Arab region, in order to reach effective solutions and ways that protect the latter from the danger of obliterating the features of identity.